Aktivitas Komunikasi Pemasaran Dinas Pariwisata Dan Kebudayaan Kabupaten Karo Dalam Meningkatkan Kunjungan Wisatawan (Studi Deskriptif Kualitatif Wisata Bukit Gundaling Berastagi) - Virginia Verby Sinuhaji; Nina Siti Salmaniah Siregar; Bahrum Jamil (Universitas Medan Area, 2019)
This study aims to determine the marketing communication activities of the Karo District Tourism and Culture Office in increasing tourist visits and to find out the supporting and inhibiting factors of the Karo District Tourism and Culture marketing communication activities. This research is a qualitative descriptive study, a technique that describes, describes and interprets the object under study systematically so that researchers can find out how marketing communication activities through observation and in-depth interviews with informants. The results of this study are marketing communication activities carried out by the Karo Regency Tourism and Culture Office, namely Advertising, Sales Promotion, and Personal Selling. This activity is carried out to increase tourist arrivals, especially Bukit Gundaling. Supporting factors to attract tourist visits are the potential of Bukit Gundaling attractions such as the natural beauty and the cool air and the visible peak of Mount Sinabung. And also social media that are currently in demand by young people which facilitates the dissemination of information about the Bukit Gundaling tourist attraction. Barriers from the marketing communication activities of the Karo Regency Tourism and Culture Office are minimal budget, lack of coordination with other agencies, and infrastructure that must be improved.